ANALISIS PENGARUH SARANA PRA-SARANA TERHADAP KEPUASAN PASIEN DI PUSKESMAS LABUHAN LOMBOK - Yogi Andreawan; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Muhammad Aditya Rachman; Wahyu Aprilyaningsih (Nusadaya Journal of Multidiciplinary Studies, 2025)
Based on the results of the t-test and R-test, it can be concluded that the variable x has a real and quite strong influence on y. From the t-test, it is known that the coefficient value for x is 1.175 with a significance value of 0.000. Because this number is smaller than 0.05, it means that the influence of x on y is very significant or really exists, not happening by chance. Meanwhile, from the R-test, the value of R = 0.722 is obtained, which indicates that the relationship between x and y is quite strong and positive. In addition, the R Square value = 0.521 means that approximately 52% of changes in y can be explained by x, while the rest is influenced by other factors outside the model. Simply put, these two tests both show that x does indeed influence and is closely related to y, and this model can be used to predict the value of y based on x.